Correction: The vascular niche in next generation microphysiological systems. Issue 18 (2nd September 2021) - Ewald, Makena L.; Chen, Yu-Hsi; Lee, Abraham P.; Hughes, Christopher C. W.
Abstract : Correction for 'The vascular niche in next generation microphysiological systems' by Makena L. Ewald et al., Lab Chip, 2021, DOI: ; 10.1039/d1lc00530h .